![image](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%20%2B%20y%7D%20%20%2B%20%20%5Csqrt%7Bx%20-%20y%7D%20%20%3D%2010%20%5C%5C%20%20%5Csqrt%7B%20%7Bx%7D%5E%7B2%7D%20-%20%20%7By%7D%5E%7B2%7D%20%20%7D%20%20%3D%209%20%5C%5C%20%5C%5C%20%20%5Csqrt%7Bx%20%2B%20y%7D%20%20%2B%20%20%5Csqrt%7Bx%20-%20y%7D%20%20%3D%2010%20%5C%5C%20%20%5Csqrt%7B%20%28x%20-%20%20y%29%28x%20%2B%20y%29%20%7D%20%20%3D%209%20%5C%5C%20%20%5C%5C%20a%20%3D%20%5Csqrt%7Bx%20%2B%20y%7D%20%20%20%20%5Cgeqslant%200%20%5C%5C%20b%20%3D%20%5Csqrt%7Bx%20-%20y%7D%20%20%5Cgeqslant%200%20%20%5C%5C%20%5C%5C%20a%20%2B%20b%20%3D%2010%20%5C%5C%20ab%20%3D%209%20%5C%5C%20%20%5C%5C%20b%20%3D%2010%20-%20a%20%5C%5C%20a%2810%20-%20a%29%20%3D%209%20%5C%5C%20%20%7Ba%7D%5E%7B2%7D%20%20-%2010a%20%2B%209%20%3D%200%20%5C%5C%20%28a%20-%209%29%28a%20-%201%29%20%3D%200%20%5C%5C%20a_1%3D%209%20%20%3D%20%20%3Eb_1%20%3D10%20-%20a_1%20%20%3D%201%5C%5C%20a_2%20%3D%201%20%20%3D%20%20%3E%20b_2%20%3D10%20-%20a_2%20%3D%209%20%5C%5C%20%20%5C%5C%20)
b_1 =10 - a_1 = 1\\ a_2 = 1 = > b_2 =10 - a_2 = 9 \\ \\ " alt=" \sqrt{x + y} + \sqrt{x - y} = 10 \\ \sqrt{ {x}^{2} - {y}^{2} } = 9 \\ \\ \sqrt{x + y} + \sqrt{x - y} = 10 \\ \sqrt{ (x - y)(x + y) } = 9 \\ \\ a = \sqrt{x + y} \geqslant 0 \\ b = \sqrt{x - y} \geqslant 0 \\ \\ a + b = 10 \\ ab = 9 \\ \\ b = 10 - a \\ a(10 - a) = 9 \\ {a}^{2} - 10a + 9 = 0 \\ (a - 9)(a - 1) = 0 \\ a_1= 9 = >b_1 =10 - a_1 = 1\\ a_2 = 1 = > b_2 =10 - a_2 = 9 \\ \\ " align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%20%5Csqrt%7Bx%20%2B%20y%7D%20%20%3D%209%20%5C%5C%20%20%5Csqrt%7Bx%20-%20y%7D%20%20%3D%201%20%5C%5C%20x%20%2B%20y%20%3D%2081%20%5C%5C%20x%20-%20y%20%3D%201%20%5C%5C%202x%20%3D%2082%20%3D%20%20%3E%20x_1%20%3D%2041%20%3D%20%20%3E%20y_1%20%3D%2040%5C%5C%20%20%5C%5C%20%5Csqrt%7Bx%20%2B%20y%7D%20%20%3D%201%20%5C%5C%20%20%5Csqrt%7Bx%20-%20y%7D%20%20%3D%209%20%5C%5C%20x%20%2B%20y%20%3D%201%20%5C%5C%20x%20-%20y%20%3D81%20%5C%5C%202x%20%3D%2082%20%3D%20%20%3E%20x_2%20%3D%2041%20%3D%20%20%3E%20y_2%20%3D%20%20-%2040%20%5C%5C%20%20%5C%5C%20%20)
x_1 = 41 = > y_1 = 40\\ \\ \sqrt{x + y} = 1 \\ \sqrt{x - y} = 9 \\ x + y = 1 \\ x - y =81 \\ 2x = 82 = > x_2 = 41 = > y_2 = - 40 \\ \\ " alt=" \sqrt{x + y} = 9 \\ \sqrt{x - y} = 1 \\ x + y = 81 \\ x - y = 1 \\ 2x = 82 = > x_1 = 41 = > y_1 = 40\\ \\ \sqrt{x + y} = 1 \\ \sqrt{x - y} = 9 \\ x + y = 1 \\ x - y =81 \\ 2x = 82 = > x_2 = 41 = > y_2 = - 40 \\ \\ " align="absmiddle" class="latex-formula">
Ответ